تطور الأسطول التجاري السوري في الربع الأخير من القرن العشرين - شلوف, محمد; صليبه, سائر (Latakia University Journal -Engineering Sciences Series, 2019)
شهد الأسطول التجاري السوري في السنوات الأخيرة من القرن العشرين تطوراً ملحوظاً من ناحية الحجوم والمحمول والعدد والنوع, لكنه أخذ في بدايات القرن الجديد يعاني من صعوبات ناتجة عن عوامل اقتصادية وإدارية وفنية، منها مثلاً عمر الأسطول وقدمه, مما أضعف قدرته على المنافسة, وخلق بعض الأزمات لم تُجدِ محاولات حلها. وزاد الأزمة تفاقماً, استحقاقات تطبيق الاتفاقيات الدولية البحرية وتعديلاتها الجديدة التي فرضت التزامات على الأسطول خلقت الحاجة إلى خبرات فنية عالية, واستخدام تجهيزات عالية التقنية والتكاليف, مما أدى لصعوبات مادية وإدارية, وعجز عن الالتزام بالمتطلبات الجديدة, وزاد هذه الصعوبات قيام رقابة الموانئ العالمية المرتبطة بتفاهمات إقليمية ودولية بالتشدد في تطبيق قواعد ومعايير الاتفاقيات وتعديلاتها, وتضييق الخناق على السفن والشركات، مما جعل السفينة خاضعة للرقابة بشكل دائم ومستمر. ندرس في هذا البحث وضع الأسطول التجاري السوري بتحليل أسباب الأزمة التي يتعرض لها من النواحي الفنية والإدارية، وعمر الأسطول، للاستفادة منها مستقبلاً لتفادي أزمات مماثلة. The Syrian commercial fleet witnessed a notable development in the last quarter of the twentieth century in terms of size, tonnage, number and type, but at the beginning of the new century it began to suffer some difficulties caused by economic, administrative and technical reasons such as the age of the fleet, weakening its ability to compete and creating numerous crises, which defied all attempts to solve them. Making things more difficult was the fact that the international maritime conventions and their new amendments were in due time for application. This imposed commitments on the fleet, creating a need for high expertise and the use of modern high-tech expensive equipment, and also leading to administrative and financial difficulties and an inability to commit to the new requirements. These difficulties were increased by the fact that international ports state-control, which was tied to regional and international understandings, became extreme in the application of these conventions and their amendments, rules and regulations, and giving less room for ships and companies, making the ship under continuous and heavy control. In this research, the status of the fleet is studied by analyzing the causes of the current crisis both technically and financially, and the age of the fleet, in order to benefit from them in the future and to avoid similar crises.